Analyzing Regional Climate Change in Africa in a 1.5, 2, and 3°C Global Warming World. Issue 4 (20th April 2018) - Weber, T.; Haensler, A.; Rechid, D.; Pfeifer, S.; Eggert, B.; Jacob, D.
Abstract: At the 21st session of the United Nations Framework Convention on Climate Change Conference of the Parties (COP21) in Paris, an agreement to strengthen the effort to limit the global temperature increase well below 2°C was decided. However, even if global warming is limited, some regions might still be substantially affected by climate change, especially for continents like Africa where the socio‐economic conditions are strongly linked to the climatic conditions. In the paper we will discuss the analysis of indices assigned to the sectors health, agriculture, and infrastructure in a 1.5, 2, and 3°C global warming world for the African continent. For this analysis an ensemble of 10 different general circulation model‐regional climate model simulations conducted in the framework of the COordinated Downscaling EXperiment for Africa was investigated. The results show that the African continent, in particular the regions between 15°S and 15°N, has to expect an increase in hot nights and longer and more frequent heat waves even if the global temperature will be kept below 2°C. These effects intensify if the global mean temperature will exceed the 2°C threshold. Moreover, the daily rainfall intensity is expected to increase toward higher global warming scenarios and will affect especially the African Sub‐Saharan coastal regions. Key Points: The African continent has to expect an increase in hot nights and longer and more frequent heat waves Daily rainfall intensity is expected to increase toward higher global warming scenarios for the African Sub‐Saharan coastal regions Major changes of the analyzed climate indices for Africa could be prevented by keeping below the 1.5°C/2°C global warming thresholds